OPTIMIZATION OF THE REGIONAL STROKE REGISTER SPECIFICATION AND EXPECTATION OF THE IMPLEMENT EFFECTIVENESS IN THE QUALITY ALTERATIONS OF RENDERING MEDICAL CARE - Фікс, Д. О.; Руденко, Г. С.; Московко, Г. С.; Московко, С. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The purpose of this article is the necessity of creation regional and after it national stroke register. Authors emphasized the necessity of creation register initiated by ESO (European stroke organization) RES-Q and Angel’s. Register is not only the implement of the quality control of rendering specialized medical care but monitoring the quality of special qualified care stroke patients receive. In this article thoroughly covered the system of rendering medical care to the stroke-suffering patients on second and third specialized levels in Vinnitsa region.